Country Governance and Corporate Governance as determinants of Firm Efficiency; Empirical Study of Pakistan - Muhammad Nisar Khan; Dr. Muhammad Ilyas; Dr. Saima Urooge (Journal of Business & Tourism, 2021)
Financial Crisis Inquiry Commission (FCIC) report of 2011 state that financial crises and failure of large corporation is due to weak governance system. Therefore, governments and regulatory bodies are convinced to ensure effective CG practices and strict regulatory requirements must be imposed. The primary aim of this research is to examine the effect of corporate governance both at country and firm-level on the firm’s efficiency of Pakistani listed non-financial firms. The empirical analyses consist of two parts. Initially firm efficiencies such as overall technical efficiency, Pure Technical efficiency and Scale efficiency are measured through Data Envelopment Analysis (DEA) technique over a 10 years’ period from 2008 to 2017.These efficiency scores are used as proxies for firm performance. In the second stage, CGboth at firm and country level are used as independent variables to examine its impact on firm efficiencies scores. The results findings support the theoretical justifications that efficient system of CG and regulatory system ensures disclosures. These disclosures not only enhance accounting information quality but also help in reducing agency cost which in return improve investors protection. Thus, managers tend to take decisions in the best interest of shareholder by utilizing firm resources efficiently and effectively and as a result enhance firm efficiency.